Simultaneous removal of nitrate and sulfate using an up-flow three-dimensional biofilm electrode reactor: Performance and microbial response. (December 2020) - Tang, Qi; Sheng, Yanqing; Li, Changyu; Wang, Wenjing; Liu, Xiaozhu
Graphical abstract: Highlights: Efficient nitrate and sulfate removal were achieved in 3D-BER. High current and short HRT decreased nutrients removal efficiency. DB dominated in lower while SRB dominated in upper part of 3D-BER. Sulfide oxidation products could serve as electron donors to enhance nitrate removal. Abstract: Nitrate removal from low carbon water is a problem in the water treatment, especially in the presence of high sulfate. In this work, an up-flow three-dimensional biofilm electrode reactor (3D-BER) was established to remove nitrate and sulfate from low organic carbon water. Results indicated that sulfate negatively affected nitrate removal. Moreover, high electric current and short hydraulic retention time deteriorated the performance of nitrate and sulfate removal. When the influent of SO4 2− was 150 mg/L, the removal efficiency of NO3 − -N and SO4 2− was 88.49 ± 4.5% and 29.35 ± 5.5%, respectively. The high-throughput sequencing revealed that denitrifying bacteria dominated in the lower part of the reactor while sulfate reducing bacteria dominated in the upper part of the reactor. It was speculated that oxidation products of sulfide could serve as supplementary electron donors to enhance nitrate removal in the 3D-BER.